2017
DOI: 10.4038/cjs.v46i4.7468
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative observations of Cyanobacteria and Dinoflagellata in reservoirs of Sri Lanka

Abstract: Abstract:. Cyanobacterial and dinoflagellate blooms have a range of social, environmental and economic impacts due to their potential of toxin production under extreme environmental conditions. Therefore, the present study aimed to understand the species abundance, distribution and the relationship between species distribution and measured environmental variables within the 45 reservoirs studied, covering three major climatic regions of Sri Lanka (Wet, Intermediate and Dry). Plankton samples were obtained usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Thus, it is imperative that a trade‐off is achieved in reservoir management to maintain water quality suitable for human consumption, while also supporting food fish production. This is particularly important because there are concerns about increasing trends of eutrophication in Sri Lankan reservoirs, resulting in a proliferation of toxigenic cyanobacteria such as Microcystis (Jayatissa et al, ; Senanayake & Yatigammana, ; Sethunge & Manage, ). In reservoirs in the Mekong River basin, for example, increased densities of bloom‐forming cyanobacteria ( Dolichospermum spp.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is imperative that a trade‐off is achieved in reservoir management to maintain water quality suitable for human consumption, while also supporting food fish production. This is particularly important because there are concerns about increasing trends of eutrophication in Sri Lankan reservoirs, resulting in a proliferation of toxigenic cyanobacteria such as Microcystis (Jayatissa et al, ; Senanayake & Yatigammana, ; Sethunge & Manage, ). In reservoirs in the Mekong River basin, for example, increased densities of bloom‐forming cyanobacteria ( Dolichospermum spp.)…”
Section: Discussionmentioning
confidence: 99%
“…Nutrient enrichment in reservoirs can cause noticeable changes in reservoir trophic status and may increase harmful algal blooms. Yatigammana and Cumming (2016) noted that Sri Lankan reservoirs could be categorized as phosphate-limited systems, although Jayatissa, Silva, McElhiney, and Lawton (2006) and Senanayake and Yatigammana (2017) argued that there would be a potential risk of increasing toxigenic algae such as Microcystis in irrigation reservoirs of Sri Lanka. This situation is even serious from a human health perspective because a proliferation of toxigenic algae in some Sri Lankan reservoirs that supply drinking water has been reported by Sethunge and Manage (2010).…”
Section: Introductionmentioning
confidence: 99%
“…The water quality variation in Sri Lanka was driven by several natural (geographical and climatic) and anthropogenic factors [14,17,19,20,38]. We categorized them two-fold: precipitation, temperature, wind speed, average water depth, elevation as natural drivers, and population density and Normalized Difference Vegetation Index (NDVI) as anthropogenic factors.…”
Section: Geographical Climatic and Anthropogenic Datamentioning
confidence: 99%
“…Here, we also showed that temperature was negatively associated with Z SD in intermediate zone reservoirs. This was probably due to the availability of favorable temperature conditions for the growth of phytoplankton in these reservoirs [17,58].…”
Section: Surface Water Transparency and Driving Forcesmentioning
confidence: 99%
See 1 more Smart Citation